Opportunity to change Lebanon’s asylum policy - Trad, S (Refugee Studies Centre, University of Oxford, 2014)
Lebanon’s attitude towards the ‘Syrian exception’ can be used as the starting point for its policy to come into line with international refugee and human rights norms, standards and protection.